Efficacité et déterminations des pratiques d'Aide Personnalisée à l'école primaire : une approche didactique - Marie Toullec-Théry; Corinne Marlot (Nantes Université, 2012)
This research in progress, leans on the didactic analysis of two cases studies. We focus our work on the practices of two teachers in primary school, within the framework of "personalized aid" recent devices. From the characteristics of the aid given in class by the teacher, we try to define which shape could the personalized aid takes. Our research shows the teachers simplify the learning at stake by splitting up and scattering the "learning games". The consequence of this simplification develops some automatisms, for the students. So, it becomes impossible for them connecting again with the didactic time of the class.